2023
DOI: 10.1128/spectrum.03339-22
|View full text |Cite
|
Sign up to set email alerts
|

The Global Success of Mycobacterium tuberculosis Modern Beijing Family Is Driven by a Few Recently Emerged Strains

Abstract: The recent population dynamics of the global tuberculosis epidemic are heavily shaped by Mycobacterium tuberculosis complex (MTBC) strains with enhanced transmissibility. The infamous Beijing family strain stands out because it has rapidly spread throughout the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…The tremendous success of Mtb as a pathogen can be explained by its co-evolution with that of the host. Strains from the Beijing family are among the most successful, as demonstrated by their global distribution and the recurrent outbreaks they cause ( 52 ). This success is partially due to their exquisite ability to manipulate the host’s immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The tremendous success of Mtb as a pathogen can be explained by its co-evolution with that of the host. Strains from the Beijing family are among the most successful, as demonstrated by their global distribution and the recurrent outbreaks they cause ( 52 ). This success is partially due to their exquisite ability to manipulate the host’s immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The tremendous success of Mtb as a pathogen can be explained by its co-evolution with that of the host. Strains from the Beijing family are among the most successful, as demonstrated by their global distribution and the recurrent outbreaks they cause ( 53 ). This success is partially due to their exquisite ability to manipulate the host’s immune system.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that, even after becoming infected with M. tuberculosis , the natural immunity generated is not protective, although natural infection occurs via aerosol [ 44 ]. However, CDC WT was chosen as the backbone for this vaccine due to its immunogenic nature, despite being from a marginal lineage as compared to the epidemic-associated, BCG-resistant Bejing strains of M. tuberculosis [ 45 , 46 ]. M. tuberculosis CDC1551 has been shown to cause increased seroconversion without increased disease compared to other clinical isolates and, through a potent and early stimulation of Th1 responses in hosts, is thought to limit its own infection and have longer survival times despite having similar bacterial burdens to other strains [ 27 , 28 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…From these studies, we chose mosR as a deletion candidate, as it was the most highly upregulated gene in murine lungs at multiple timepoints (28,45, and 60 days post-infection) when compared to M. tuberculosis in culture; upon further study, it was revealed to be an operon controlling gene involved in late-stage mycobacterial survival [17,19]. The single deletion of mosR in the H37Rv backbone was shown to be highly attenuated via the aerosol route and the single deletion in the CDC1551 backbone was shown to be a safe and effective vaccine in a previous study [19,20].…”
Section: Introductionmentioning
confidence: 99%